ENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. MEDIA NUSANTARA INFORMASI BIRO JAWA TIMUR - Prabowo, Anindita Lakmi (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2019)
Human resources play a very important as human as the wheels of all company activities. Efforts to improve the performance of the system conducted well-defined leadership and motivation to improve employee morale. This study aims to examine and analyze the influence of transformational leadership and work motivation on the performance of employees of PT. Media Nusantara Informasi Jawa Timur Bureau. Data were collected used survey through questionnaires and carried out at 50 employees of PT. MNI Bureau of Jawa Timur. Data analysis in this study used SPSS version 17. The technique used is purposive sampling and testing techniques of data used in this study include testing the validity of the factors, testing reliability analysis with Cronbach's alpha. Analysis of data used multiple linear regression analysis, to test and prove the research hypotheses. The analysis showed that transformational leadership has a positive effect on employee performance and work motivation positive effect on employee performance. Keyword: Transformational leadership, motivation to work, performance of employees.